INTEGRASI EPISTEMOLOGI ISLAM: HADARAT AL-NAS, HADARAT AL-ʿILM, DAN HADARAT AL-FALSAFAH DALAM KERANGKA PENDIDIKAN ISLAM KONTEMPORER - Muhammad Nadhif Syuhada; Eva Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Contemporary Islamic education faces the challenge of a dichotomy between religious knowledge and general knowledge, which has resulted in partial educational practices, both normative and dogmatic and value-free positivism. This situation demonstrates the importance of strengthening an integrative epistemological foundation so that Islamic education can respond to current developments without losing its Islamic identity. This article aims to examine the concept of integrating Islamic epistemology through the framework of Hadarat al-Nas, Hadarat al-ʿIlm, and Hadarat al-Falsafah in the context of contemporary Islamic education. This study uses a qualitative approach with library research. Data were obtained from various literature sources, including books, scientific journal articles, and academic works relevant to Islamic epistemology, Islamic educational philosophy, and contemporary Islamic educational thought. The results indicate that the integration of Hadarat al-Nas, Hadarat al-ʿIlm, and Hadarat al-Falsafah forms a holistic and complementary Islamic epistemological framework. Hadarat al-Nas serves as a normative foundation based on revelation, Hadarat al-ʿIlm as scientific and empirical rationality, and Hadarat al-Falsafah as a space for critical reflection on the meaning and ethical implications of knowledge. The integration of these three has implications for the development of Islamic education that is not only oriented towards mastery of knowledge, but also towards character formation, moral awareness, and social responsibility. Thus, integrative Islamic epistemology serves as a strategic foundation for formulating a paradigm for Islamic education that is relevant, balanced, and oriented towards civilizational development.